2008
DOI: 10.1021/ol8008792
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indolines via a Domino Cu-Catalyzed Amidation/Cyclization Reaction

Abstract: A highly efficient one-pot procedure for the synthesis of indolines and their homologues based on a domino Cu-catalyzed amidation/nucleophilic substitution reaction has been developed. Substituted 2-iodophenethyl mesylates and related compounds afforded the corresponding products in excellent yields. No erosion of optical purity was observed when transforming enantiomerically pure mesylates under the reaction conditions.The indoline moiety 1 can be found in numerous biologically active alkaloid natural product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…The residue was purified by column chromatography (pentane/ethyl acetate=95:5) to give the title compound as a light yellow oil (2.94 g, 84 %). The 1 H and 13 C spectra were in accord with the literature …”
Section: Methodssupporting
confidence: 61%
“…The residue was purified by column chromatography (pentane/ethyl acetate=95:5) to give the title compound as a light yellow oil (2.94 g, 84 %). The 1 H and 13 C spectra were in accord with the literature …”
Section: Methodssupporting
confidence: 61%
“…catalyzed amidation reactions as one of its key strategies in the synthesis of the alkaloid vasicoline [37]. Again, Buchwald et al also reported a domino Cu(I) catalyzed amidation/nucleophilic substitution protocol to access substituted indolines, a very important and common structural motif in many bioactive natural products [38].…”
Section: Resultsmentioning
confidence: 99%
“…The clean inversion observed at the mesylate center strongly indicates the occurrence of an S N 2 substitution process. 141 The reaction can also be used to synthesize 6- and 7-membered rings and a range of nitrogen protecting groups including Boc, Cbz and acetyl are compatible.…”
Section: Applications In the Synthesis Of Heterocyclesmentioning
confidence: 99%